Attack-defense game model of node traces privacy preserving for vehicle ad hoc networks - Wei-dong YANG; Yun-hua HE; Li-min SUN (Tongxin xuebao)
The vulnerability of published vehicle traces is a focus issue for vehicle ad hoc network. Aiming at the privacy of published traces with a game-theoretic model under the scene of the active attacks and defense actions were modeled, and the attack and defense games were analyzed. Also ability of an adversary and the goal that a defender wants to achieve by the information entropy were quantified. By the analysis of true traces, the Nash equilibrium point under the game of complete information and an optimal defense strategy providing the user with the best privacy level for each at-tack strategy were presented.